APLIKASI PENDAFTARAN ONLINE SISWA BARU SMA INSTITUT INDONESIA SEMARANG (Information Technology and Telematics, 2013)
ABSTRAK   High school Institut Indonesia Semarang as one of the schools that organizes educational activities in new admissions was by coming directly to the school. Schools not use online media as the media registration online so that people receive the information in a straightforward and does not need to come to school. Admission online course selection system is the admission of new students, starting from the registration process, the selection up to the announcement of the selection results. With the delivery of information to the online media is expected to facilitate new admissions to increase recruitment of new students achievement is not maximized. PSB Online information system is designed using Macromedia Dreamweaver 6.0 tool case and built using PHP programming language and MySQL database. System information can be accessed by the administrator or PSB officers, general public and prospective students.   Keywords: application, online registration